2020
DOI: 10.3390/cells9030645
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNAs in Small Extracellular Vesicles Indicate Successful Embryo Implantation during Early Pregnancy

Abstract: Synchronous communication between the developing embryo and the receptive endometrium is crucial for embryo implantation. Thus, uterine receptivity evaluation is vital in managing recurrent implantation failure (RIF). The potential roles of small extracellular vesicle (sEV) miRNAs in pregnancy have been widely studied. However, the systematic study of sEVs derived from endometrium and its cargos during the implantation stage have not yet been reported. In this study, we isolated endometrium-derived sEVs from t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 43 publications
(19 citation statements)
references
References 53 publications
0
19
0
Order By: Relevance
“…Among them, miR-30d was observed to be encapsulated in EVs and released by primary human endometrial epithelial cells (hEECs) and transferred to the trophectoderm of murine embryos when co-cultured, thus regulating genes related to embryonic adhesion and promoting embryo implantation [8]. MicroR-34c-5p was found to be differentially enriched in EVs isolated from mouse endometrium during different phases of pregnancy, and it is likely to target GAS1 (Growth Arrest Specific 1) and influence embryo implantation [119]. In sheep, a clear influence of progesterone-mediated regulation of miRNA content in EVs isolated from the uterine lumen was reported [120].…”
Section: Extracellular Vesicle Molecular Cargo In Animal Reproduction and Embryo-maternal Cross-talkmentioning
confidence: 99%
“…Among them, miR-30d was observed to be encapsulated in EVs and released by primary human endometrial epithelial cells (hEECs) and transferred to the trophectoderm of murine embryos when co-cultured, thus regulating genes related to embryonic adhesion and promoting embryo implantation [8]. MicroR-34c-5p was found to be differentially enriched in EVs isolated from mouse endometrium during different phases of pregnancy, and it is likely to target GAS1 (Growth Arrest Specific 1) and influence embryo implantation [119]. In sheep, a clear influence of progesterone-mediated regulation of miRNA content in EVs isolated from the uterine lumen was reported [120].…”
Section: Extracellular Vesicle Molecular Cargo In Animal Reproduction and Embryo-maternal Cross-talkmentioning
confidence: 99%
“…Our group recently proposes another possible pattern of EVs functioning during implantation with miRNAs cargos. Compared to the pre-implantation period, content of miR-34c-5p, miR-210, miR-369-5p, miR-30b, and miR-582-5p in endometrium-derived sEVs is remarkably increased during window of implantation (49). 2987 mRNAs as potential targets of these miRNAs are mainly enriched in the phosphatidylinositol 3 kinase/protein kinase B signaling pathway, mitogen-activated protein kinase signaling pathway, focal adhesion, cell-cell adhesion, and extracellular exosome (49).…”
Section: Nucleic Acid Cargos Influence Gene Expression Of Target Cellsmentioning
confidence: 90%
“…miRNAs were already described to be secreted by EVs from embryos of different species, including human, bovine, and porcine (112,(117)(118)(119)(120). miRNAs were shown to modulate the embryonic-maternal communication, as seen by modulation of maternal genes following interactions between embryonic miRNAs and uterine cells (118,121). Analysis of miRNAs released in the embryo culture media (individually cultured embryos) has shown that embryos which established a pregnancy had 103 miRNAs (out of 621 identified miRNAs) differentially expressed when compared to embryos that did not result in a pregnancy (112).…”
Section: Ev Cargoes As Biomarkers Of Embryo Qualitymentioning
confidence: 99%